Romadhon Moon Songsong Socialization - Nurul Chamidah; Itat Tatminah; Uun Machsunah; Fikriyah (Ann Publisher, 2024)
The month of Romadhon is approaching. All Muslims are happy to welcome the month of Romadhon in 2024. Radio, YouTube, newspapers, and various educational institutions have made activities regarding the importance of the month of Ramadhan, including the University of Muhammadiyah Cirebon. On Sunday, Tabligh Akbar Songsong Romadhon was held, which was attended by the entire academic community and their families. The speaker at this event was H Fahmi Salim (Tabligh Council PP Muhammadiyah). Topics raised in this event included the superiority of Muhammadiyah in determining the initial time of fasting, Eid al-Fitr, and other worship times using the Hijri calendar, not the Gregorian calendar based on the sun's orbit. The purpose of the month of Romadhon is for us believers to become pious people.